On the role of tasks in virtual game-based learning: The example of “Lost in Antarctica“ - Kibler, Simone; Eckardt, Linda (Purdue University, 2018)
There is evidence that tasks play an important role in the context of the development of virtual learning scenarios. This paper will focus on this fact and identify the relationship between tasks and their purpose in the context of “Lost in Antarctica”. This game-based blended-learning scenario contains a huge variety of tasks ensuring the acquisition of different skills within the broad range of information literacy (IL)-topics. In conclusion, general recommendations for the use of tasks in the conceptional process of e-learning environments should be given. "Lost in Antarctica” is a game-based blended-learning platform for about 150 students of Industrial Engineering and Management who receive credit points for the successful completion of 12 levels representing important topics of IL. The source code of the game is available for all interested institutions. In the story-based learning scenario, the students act as scientists who travel in teams on a research expedition to the South Pole, but due to a snow storm they crashland. For the completion of each level, an airplane component can be received to repair the defective airplane. In the game, each level has a similar structure: the students have to alternately acquire knowledge and solve tasks. Opening new and innovative ways for teaching IL, the University Library of Braunschweig, the Institute of Business Information Systems (Department Information Management) of the Technische Universität Braunschweig and further strategic partners from university libraries in Hannover and Clausthal (Germany), developed this game-based blended-learning module on IL. During the creation process of the game, students as representatives of the target group were involved in the creation of the story and in the development of the ranking criteria for the game through several student innovation projects.